Ce que Charles Darwin doit à Joseph Banks - Le Guyader, Hervé (Comptes Rendus Biologies, 2024)
History has remembered Joseph Banks as the explorer-botanist of the first voyage of James Cook. Yet, shortly after his return, he got elected president of the Royal Society and, for over 40 years, he then played in Great Britain an eminent role in reorganizing natural sciences and advocating an “economic botany”. He actively intervened in acclimatization and varietal selection of plants and animals in Great Britain as in the future English colonies. Thus he built an intellectual environment which will promote the emergence of Charles Darwin’s thoughts.